Serum miRNA Signatures Are Indicative of Skeletal Fractures in Postmenopausal Women With and Without Type 2 Diabetes and Influence Osteogenic and Adipogenic Differentiation of Adipose Tissue–Derived Mesenchymal Stem Cells In Vitro. (26th September 2016) - Heilmeier, Ursula; Hackl, Matthias; Skalicky, Susanna; Weilner, Sylvia; Schroeder, Fabian; Vierlinger, Klemens; Patsch, Janina M; Baum, Thomas; Oberbauer, Eleni; Lobach, Iryna; Burghardt, Andrew J; Schwartz, Ann V; et al.
ABSTRACT: Standard DXA measurements, including Fracture Risk Assessment Tool (FRAX) scores, have shown limitations in assessing fracture risk in Type 2 Diabetes (T2D), underscoring the need for novel biomarkers and suggesting that other pathomechanisms may drive diabetic bone fragility. MicroRNAs (miRNAs) are secreted into the circulation from cells of various tissues proportional to local disease severity and were recently found to be crucial to bone homeostasis and T2D. Here, we studied, if and which circulating miRNAs or combinations of miRNAs can discriminate best fracture status in a well‐characterized study of diabetic bone disease and postmenopausal osteoporosis ( n  = 80 postmenopausal women). We then tested the most discriminative and most frequent miRNAs in vitro. Using miRNA‐qPCR‐arrays, we showed that 48 miRNAs can differentiate fracture status in T2D women and that several combinations of four miRNAs can discriminate diabetes‐related fractures with high specificity and sensitivity (area under the receiver‐operating characteristic curve values [AUCs], 0.92 to 0.96; 95% CI, 0.88 to 0.98). For the osteoporotic study arm, 23 miRNAs were fracture‐indicative and potential combinations of four miRNAs showed AUCs from 0.97 to 1.00 (95% CI, 0.93 to 1.00). Because a role in bone homeostasis for those miRNAs that were most discriminative and most present among all miRNA combinations had not been described, we performed in vitro functional studies in human adipose tissue–derived mesenchymal stem cells to investigate the effect of miR‐550a‐5p, miR‐188‐3p, and miR‐382‐3p on osteogenesis, adipogenesis, and cell proliferation. We found that miR‐382‐3p significantly enhanced osteogenic differentiation ( p  < 0.001), whereas miR‐550a‐5p inhibited this process ( p  < 0.001). Both miRNAs, miR‐382‐3p and miR‐550a‐5p, impaired adipogenic differentiation, whereas miR‐188‐3p did not exert an effect on adipogenesis. None of the miRNAs affected significantly cell proliferation. Our data suggest for the first time that miRNAs are linked to fragility fractures in T2D postmenopausal women and should be further investigated for their diagnostic potential and their detailed function in diabetic bone. © 2016 American Society for Bone and Mineral Research.